Kemampuan Komunikasi Orang tua Terhadap Perkembangan Emosional Anak Sekolah Dasar - Mansyur Babuta Tomayahu; Sri Susanti Papuke; Novie Yuliani Sumiran (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2020)
Background: Parents are the first social group that becomes the center of child identification, so that the emotional development of children can be controlled by parents, this can prevent children from doing things that are not wanted.Objective: This study aims to determine the communication skills of parents with children's emotional development. Methods: The study used a cross-sectional design. The sample is 57 children in grades 1-4. The sampling technique used purposive sampling method. Results: Based on the results of the study, 37.8% of students showed caring behavior in the sufficient category, 35.6% in the good category and 26.7% showed less caring behavior. Conclusion: there is a relationship between parents' communication skills with the emotional development of elementary school children grades 1-4